2003
DOI: 10.1046/j.1365-263x.2003.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Molar incisor hypomineralization: a questionnaire inventory of its occurrence in member countries of the European Academy of Paediatric Dentistry (EAPD)

Abstract: Paediatric dentists in Europe are aware of MIH and the majority consider it to be a clinical problem. Only limited data are available on the prevalence of MIH. Comparable and representative prevalence studies are therefore urgently needed to gain more knowledge about the magnitude of MIH and related clinical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
1
30

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 9 publications
11
89
1
30
Order By: Relevance
“…The selection of schools was through simple random sampling, processed by the BioEstat 5.0 software, according to the listing of students provided by the management of schools and considering a sample previously stipulated by researchers of 300 students, 100 of each school since the European Academy of Pediatric Dentistry (EAPD) recommends that for MIH diagnosis in epidemiological studies, at least 100 people should be examined [23].…”
Section: Methodsmentioning
confidence: 99%
“…The selection of schools was through simple random sampling, processed by the BioEstat 5.0 software, according to the listing of students provided by the management of schools and considering a sample previously stipulated by researchers of 300 students, 100 of each school since the European Academy of Pediatric Dentistry (EAPD) recommends that for MIH diagnosis in epidemiological studies, at least 100 people should be examined [23].…”
Section: Methodsmentioning
confidence: 99%
“…(Weerheijm & Mejare, 2003) Lately, a systematic review showed a wide variation in the prevalence of MIH (2.4 -40.2 %) and stated that the cross comparison of the results of the various studies were difficult because of use of different indices and criteria, examination variability, methods of recording and different age groups. (Jalevik, 2010) Based on this, we performed a nonsystematic hand-searching screening in the PUBMED data base using the terms: EAPD; MIH; limited to: at least 100 subjects and the data of study -after 2003 and the results could be found (Table 3).…”
Section: Prevalence Of Mihmentioning
confidence: 99%
“…In its initial stage, this enamel has a high degree of brittleness, which can easily break, causing severe discomfort and sensitivity, especially to temperature changes, air and tooth brushing [5].…”
Section: Introductionmentioning
confidence: 99%
“…[18] In Brazil, studies have shown prevalence from 12.3% [14] to 40% [19]. Different prevalence rates among studies may be due to the different locations in which they were carried out, but it is possible that different diagnostic criteria may also contribute to these different results [5].…”
Section: Introductionmentioning
confidence: 99%